Mixed reality as a time-efficient alternative to cadaveric dissection. (2nd August 2020) - Ruthberg, Jeremy S.; Tingle, Galen; Tan, Lisa; Ulrey, Lauren; Simonson-Shick, Sue; Enterline, Rebecca; Eastman, Henry; Mlakar, Jeffrey; Gotschall, Robert; Henninger, Erin; Griswold, Mark A.; Wish-Baratz, Susanne
Abstract: Objectives : The extent of medical knowledge increases yearly, but the time available for students to learn is limited, leading to administrative pressures to revise and reconfigure medical school curricula. The goal of the present study is to determine whether the mixed reality platform HoloAnatomy represents an effective and time-efficient modality to learn anatomy when compared to traditional cadaveric dissection. Methods: This was a prospective, longitudinal study of medical students completing a musculoskeletal anatomy course at Case Western Reserve University School of Medicine. Participants were divided into two groups based on learning platform (HoloAnatomy versus traditional cadaveric dissection) and content area (upper limb versus lower limb anatomy). Time spent in lab and end of course practical exam scores were compared between groups. Results: The average study time of 48 medical students who completed study requirements was 4.564 h using HoloAnatomy and 7.318 h in the cadaver lab ( p  = 0.001). No significant difference was found between exam scores for HoloAnatomy and cadaver learners ( p  = 0.185). Conclusions: Our results indicate that HoloAnatomy may decrease the time necessary for anatomy didactics without sacrificing student understanding of the material.